Optimalisasi Destinasi Wisata Alam Dan Digitalisasi Umkm Melalui Program Kuliah Kerja Nyata Di Desa Cilengkrang Sumedang - Muhammad Fadillah Aldiansyah; Nabila Putri Iskandar; Nurwulan Fitriani; Septy Amalia; Adang Sudrazat (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
Cilengkrang Village in Sumedang Regency boasts natural tourism attractions such as Cakrabuana Waterfall and a local UMKM product, Jamparing Coffee. However, its development has been hindered by a lack of appealing facilities, insufficient signage, and traditional marketing strategies. This community service program, conducted through the Student Community Service (KKN) initiative, aims to maximize natural tourism potential and expand market reach for the local MSME by leveraging digital technology. A descriptive-qualitative methodology was employed, encompassing stages such as observation, interviews, partnership collaboration, field implementation, and outcome evaluation. The findings indicate that: (1) an aesthetic, nature-themed photo spot was established at Cakrabuana Waterfall to create an "Instagrammable" attraction; (2) directional signage was installed at strategic locations to improve accessibility and visitor convenience; and (3) a creative promotional video utilizing a storytelling approach was produced and published on Instagram and TikTok for Jamparing Coffee. The program successfully attracted greater attention to the destination, facilitated visitor navigation, and strengthened brand awareness for the local product. This initiative concludes that integrating physical facility improvements with digital promotion can foster sustainable village economic growth through active community engagement.